Two types of immunoglobulin-negative Abelson murine leukemia virus-transformed cells: implications for B-lymphocyte differentiation. - Hagiya, M (1986)
Both alleles of immunoglobulin (Ig) heavy-chain joining region (JH) genes in three Ig-negative Abelson murine leukemia virus (Ab-MuLV)-transformed cell lines were characterized by DNA cloning and nucleotide sequence determination. These studies unambiguously identified two distinct types of Ig-negative B-lineage cells. The first type of cell (e.g., R8) is an "immature pre-B cell," and it contains at least one intermediate recombinant structure containing heavy-chain diversity (DH) and JH sequences but no variable region (VH) sequence. This type of cell, which has also been characterized by other investigators, generates mu-positive sublines during subsequent culturing of cells and represents a precursor stage to pre-B cells. The second type of cell (e.g., RAW253) is an "abortive pre-B cell," in that both JH alleles contain nonfunctional VH-DH-JH structures. The nucleotide sequence determinations in this study demonstrated that these nonfunctional V-D-J structures were generated by nonproductive somatic recombinations, involving either out-of-phase joining events, or the formation of termination codons in the DH coding sequences. The identification of abortive pre-B cells suggests that the recombinational joining of Ig VH, DH, and JH segments is not actively regulated by a putative recombinase to preserve the translational reading frame. This in turn implies that a large portion of precursor cells at the early stage of B-cell differentiation are abortive and possibly blocked to further differentiation.